Surveying the Academic Literature on the Use of OKR (Objectives and Key Results) – An Update - Silva, Roberto; Santos, Gleison (iSys - Journal of Information Systems, 2024)
OKR (Objectives and Key Results) emerged as a lightweight framework for business objectives measurement and strategic alignment. Although there is growing interest in OKR, academic literature on the subject is still scarce. Most importantly, there is limited knowledge about the difficulties, benefits, and lessons learned from its use. We executed a systematic mapping study. We found 47 studies and identified associated difficulties, benefits, and lessons learned. In general, OKR use is under-documented from a theoretical point of view. Among the topics associated with using OKR are communication, performance evaluation, task planning and prioritization, transparency, team alignment, and goal fulfillment. We found few academic studies addressing the topic in depth. We expect this study to serve as a basis for other researchers to continue to seek and deepen the understanding of how to support the use of OKR and, thus, help build knowledge on the subject.